First-year college performance: a study of home-schooled graduates and traditional high school graduates - Jones, Paul Anthony, author; Gloeckner, Gene W., advisor; Morgan, George A., committee member; Lehmann, Jean P., committee member; Bomotti, Sally S., committee member (Colorado State University. Libraries, 2002)
The purpose of this study was to determine if there were differences in first-year academic performance between home-schooled and traditional high school graduates in college measured by grade point average, retention. ACT test scores, and credits earned in their first year of college. Additionally, the study examined the attitudes and perceptions of admission personnel toward the home-schooled graduate. A total of 55 home-schooled graduates and 53 traditional high school graduates were examined in the first phase of the study. No significant differences were found between home-schooled and traditional high school graduates in first-year grade point average, retention. ACT test scores, or credits earned in the first year of college, but the home-schooled graduates were somewhat higher on all of these measures. A significant correlation was found between ACT Composite test scores and retention, cumulative grade point average, and cumulative credits earned. The second phase of the study included 55 four-year admissions officers from the Western United States. The findings of this study revealed that nearly 75% of the colleges and universities had an official home school admissions policy. The ACT or SAT test was the most preferred item utilized for consideration for admission followed by an essay or GED test score. More than 55% of the admission officers expected home schooled graduates to perform about the same as traditional high school graduates on overall first-year success rate, cumulative grade point average, retention rate, credit hours earned, and coping socially in their first year of college.
Keywords: school administration; higher education; academic guidance counseling; educational administration; school counseling